Evaluation of age-hardening time on the mechanical behavior of Al-Mg-Si (Al 6063) alloy composites reinforced with alumina particles - Davies Oladayo Folorunso; Kolawole Olawumi Ogunbiyi; Seun Samuel Owoeye (Journal of Alloys and Metallurgical Systems, 2023)
This research attempts to evaluate the effects of age-hardening on the mechanical behavior of aluminum (6063) alloy reinforced with alumina (Al2O3) particles. Aluminum (6063)/Al2O3 composites containing 0, 5, 7, 9 and 10 wt% Al2O3 particles respectively were fabricated using double stir casting technique and representative samples from each composition were subjected to age-hardening treatment at 180 °C for 60 min, 120 min and 180 min respectively. The microstructures were evaluated using SEM while fracture toughness and tensile properties were used to evaluate the mechanical behavior of both the as-cast composites and their age-hardened counterparts. The microstructure evaluation reveals formation of coherent precipitates of Mg2Si evenly distributed in the age-hardened composites. Significant improvement in tensile strength values of 129.8, 88.6, 90.6, 137.9 and 170.6 MPa were obtained for the age-hardened composites compared to their as-cast composites with 42.2, 72.9, 81.2, 80.84 and 71.5 MPa across the series respectively. Similar trend was observed for fracture toughness with KIC values of 7.5, 5.8, 4.5, 7.8 and 9.6 MPam1/2 for age-hardened composites compared with 4.68, 4.64, 4.07, 4.06 and 3.59 MPam1/2 obtained for their as-cast composites. Age-hardening time of 180 min impart better tensile strength and fracture toughness.